Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11356-021-15936-6
|View full text |Cite
|
Sign up to set email alerts
|

How does economic policy uncertainty affect CO2 emissions? A regional analysis in China

Abstract: More recently, the COVID-19 pandemic outbreak has created massive economic policy uncertainty (EPU). EPU and its economic fallout have been a hot topic of study; however, the impact of EPU on CO 2 emissions has been seldom addressed to date. This paper investigates the effects of the EPU on CO 2 emissions. It elucidates the role of EPU in moderating the environmental regulation-CO 2 emissions nexus at the national and regional levels using th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 78 publications
1
22
1
Order By: Relevance
“…However, there are some gaps in the existing studies. Specifically, the conclusions are controversial (Gill et al, 2019;Shabir et al, 2021) [21,22], and while much of the literature has pointed out that EPU brings more environmentally adverse effects (Yu et al, 2021, Adedoyin andZakari, 2021) [19,23], a small number of scholars have argued that EPU does some good in reducing CO 2 emissions (Chen et al, 2021; Do gan and Güler, 2021) [24,25], and other researchers argue that there is no influence of EPU on CO 2 emissions (Abbasi and Adedoyin, 2021; Liu and Zhang, 2021) [26,27]. Additionally, most studies have utilized the EPU index given by Baker et al, (2016) [28] to measure EPU, but this index has some limitations in that it cannot reflect uncertainty related to political events and it is not calculated from a single base for different countries worldwide, which may bring about biased results (Adams et al, 2020;Atsu and Adams, 2021) [20,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some gaps in the existing studies. Specifically, the conclusions are controversial (Gill et al, 2019;Shabir et al, 2021) [21,22], and while much of the literature has pointed out that EPU brings more environmentally adverse effects (Yu et al, 2021, Adedoyin andZakari, 2021) [19,23], a small number of scholars have argued that EPU does some good in reducing CO 2 emissions (Chen et al, 2021; Do gan and Güler, 2021) [24,25], and other researchers argue that there is no influence of EPU on CO 2 emissions (Abbasi and Adedoyin, 2021; Liu and Zhang, 2021) [26,27]. Additionally, most studies have utilized the EPU index given by Baker et al, (2016) [28] to measure EPU, but this index has some limitations in that it cannot reflect uncertainty related to political events and it is not calculated from a single base for different countries worldwide, which may bring about biased results (Adams et al, 2020;Atsu and Adams, 2021) [20,29].…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of uncertainty * GDP is 0.076, which is significantly positive at 1%, suggesting that better economic performance would contribute to the reduction in the negative effect of EPU on environmental performance. This is mainly because better economic performance offers governments more power to deal with EPU; moreover, even under serious EPU, better economic performance can make it is possible for governments to allocate some fiscal expenditure to environmental protection, thus reducing the adverse environmental effects brought by EPU (Liu and Zhang, 2021) [ 39 ]. Aside from this, according to the environmental Kuznets relationship, pollution levels eventually fall as income increases.…”
Section: Estimating Resultsmentioning
confidence: 99%
“…For example, Abbasi and Adedoyin (2020) [ 36 ] examined whether the effects of EPU on carbon emissions are established in China by employing ARDL estimation based on the annual data from 1970 to 2018, and concluded that EPU cannot change the carbon emissions in China, which may be attributed to its sustainable corporate policies. Similarly, Liu and Zhang (2021) [ 39 ] offered a similar idea for the central and western region of China. On the other hand, Adedoyin and Zakari (2020) [ 36 ] proposed that the influence of EPU on CO 2 emissions is not constant short-term and long-term; specifically, while EPU reduces CO 2 emissions initially, it would increase the CO 2 emissions long-term.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the findings of these research are contradictory and diverse, depending on the methodological techniques used and the nations studied. EPU has been shown to improve environmental quality in a number of studies (Ahmed et al 2021 ; Chu and Le 2022 ; Ivanovski and Marinucci 2021 ; Liu and Zhang 2022 ; Gu et al 2021a ; Xin and Xin 2022 ; Zeng and Yue 2022 ; Chen et al 2021 ). For example, Ahmed et al ( 2021 ) reported that EPU decreases CO 2 emissions in the USA using the nonlinear autoregressive distributed lag (NARDL) technique for the period 1985–2017.…”
Section: Literature Review and Contributions Of The Studymentioning
confidence: 99%